Different responses of skeletal muscles to femoral artery ligation-induced ischemia identified in BABL/c and C57BL/6 mice - Tu, Huiyin; Qian, Junliang; Zhang, Dongze; Barksdale, Aaron N.; Wadman, Michael C.; Pipinos, Iraklis I.; Li, Yu-Long (Frontiers in Physiology, 2022)
Peripheral arterial disease (PAD) is a common circulatory problem in lower extremities, and the murine ischemic model is used to reproduce human PAD. To compare strain differences of skeletal muscle responses to ischemia, the left femoral artery was blocked by ligation to reduce blood flow to the limb of BALB/c and C57BL/6 mice. After 6 weeks of the femoral artery ligation, the functional and morphological changes of the gastrocnemius muscle were evaluated. BALB/c mice displayed serious muscular dystrophy, including smaller myofibers (524.3 ± 66 µM2), accumulation of adipose-liked tissue (17.8 ± 0.9%), and fibrosis (6.0 ± 0.5%), compared to C57BL/6 mice (1328.3 ± 76.3 µM2, 0.27 ± 0.09%, and 1.56 ± 0.06%, respectively; P < 0.05). About neuromuscular junctions (NMJs) in the gastrocnemius muscle, 6 weeks of the femoral artery ligation induced more damage in BALB/c mice than that in C57BL/6 mice, demonstrated by the fragment number of nicotinic acetylcholine receptor (nAChR) clusters (8.8 ± 1.3 in BALB/c vs. 2.5 ± 0.7 in C57BL/6 mice, P < 0.05) and amplitude of sciatic nerve stimulated-endplate potentials (EPPs) (9.29 ± 1.34 mV in BALB/c vs. 20.28 ± 1.42 mV in C57BL/6 mice, p < 0.05). More importantly, 6 weeks of the femoral artery ligation significantly weakened sciatic nerve-stimulated skeletal muscle contraction in BALB/c mice, whereas it didn’t alter the skeletal muscle contraction in C57BL/6 mice. These results suggest that the femoral artery ligation in BALB/c mice is a useful animal model to develop new therapeutic approaches to improve limb structure and function in PAD, although the mechanisms about strain differences of skeletal muscle responses to ischemia are unclear.